Clustering and multifacility location with constraints via distance function penalty methods and dc programming. (2nd November 2018) - Nam, Nguyen Mau; An, Nguyen Thai; Reynolds, Sam; Tran, Tuyen
ABSTRACT: This paper is a continuation of our effort in using mathematical optimization involving DC programming in clustering and multifacility location. We study a penalty method based on distance functions and apply it particularly to a number of problems in clustering and multifacility location in which the centers to be found must lie in some given set constraints. We also provide numerical examples to test our method.